Efficiency analysis of automotive hydrogen internal combustion engine combined with a steam rankine cycle - Mohamad, Md Nor Anuar (2010)
A hydrogen internal combustion engine (HICE) emits both heat and water from the combustion process. In this study, a new concept of heat recovery sub-system, which exploits the water exhausted from an automobile HICE as a working fluid for a steam power generation system based on the Rankine cycle has been introduced. In this cycle, the water separated from the HICE exhaust is evaporated and superheated by the exhaust waste heat of the HICE, and the water vapor is released to the atmosphere after it is used to produce power in a steam expander. The operating concept of the proposed recovery sub-system is described in this study, along with its potential power generated, and its beneficence to the overall thermal efficiency of the HICE. The recovery sub-system has been evaluated for various engine speeds using a fundamental thermodynamic model analysis. Two designs of the model have been examined; one with a condenser and another one without the condenser. The results showed that the design without a condenser is a cost-effective and simple approach, and its performance is comparable to another design. Both designs consumed almost equal amount of water as their working fluid. Consequently, it is concluded that the design without condenser is preferable for the recovery sub-system for HICE, which could enhance the overall thermal efficiency of the HICE from 27.2% to 33.6%, representing improvements of 2.9% to 3.7% from an HICE without any recovery sub-systems at engine speeds of 1500 to 4500 rpm